Peritoneal defect herniation after laparoscopic inguinal hernia repair (transabdominal preperitoneal) - A case report with review of literature - De, Anushtup; Roy, Prabal; Kumar, Sunil (Indian Journal of Case Reports, 2018)
The development of newer techniques in the field of surgery is associated with its own set of possible complications. Laparoscopic mesh repair is now widely accepted as the standard of care for inguinal hernias. Both transabdominal preperitoneal approach and totally extraperitoneal approach are almost equally popular worldwide. We report a case of intestinal obstruction following herniation of small bowel through the peritoneal defect and resultant adhesions to the mesh. We also present a literature review of instances of small bowel herniation through the peritoneal defect and resultant intestinal obstruction after inguinal hernia repair.